Isolation and Identification of Tyramine-Producing Lactic Acid Bacteria from Fermented Olives - Gülsüm Atasoy; Pınar Şanlıbaba; Rahmi Ertan Anlı (Turkish Journal of Agriculture: Food Science and Technology)
In the present study, we aimed to isolate and biochemically identify tyramine-producing lactic acid bacteria (LAB) from black and green fermented olive samples produced by traditional methods and obtained from different provinces of Turkey. A total of 36 LABs, including Enterococcus spp. (2 isolates), Lactobacillus spp. (16 isolates), and Lactococcus spp. (18 isolates) were isolated from the fermented olive samples. Among them, 27 isolates could decarboxylate tyrosine amino acid; however, the decarboxylase enzyme activity of the remaining 9 isolates was negative. The ability of LAB isolates with positive enzyme activity to produce tyramine was evaluated using high-performance liquid chromatography (HPLC), and 6 isolates were found to be significant tyramine producers in vitro, producing tyramine at concentrations ranging from 107.251 to 207.618 mg L–1.